2016
DOI: 10.15537/smj.2016.4.14835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outpatient service quality in Eastern Saudi Arabia

Abstract: Objectives:To investigate perceptions and expectations of patients regarding hospital outpatient services by using a service quality gap model and factors influencing such gaps.Methods:In this cross-sectional descriptive study conducted between October and November 2014 in the outpatient waiting areas of a hospital in the Eastern Province of Saudi Arabia, a sample of 306 patients was selected by convenience sampling technique. The data was collected through an Arabic version of the service quality (SERVQUAL) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 15 publications
13
63
1
4
Order By: Relevance
“…Dilman's study demonstrated that 85% of code green calls resulted in successful resolution of the violent incidents. 42 Preventive measures for WPV among nurses include the following: increase awareness of potentially violent patients; wear suitable clothes; maintain proper positioning when communicating with patients; keep a safe distance; maintain the correct posture; and listen actively. A study by Hill et al showed a 65% reduction in staff injuries, from 2.2 per week to 0.77 per week, during the 1 year intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Dilman's study demonstrated that 85% of code green calls resulted in successful resolution of the violent incidents. 42 Preventive measures for WPV among nurses include the following: increase awareness of potentially violent patients; wear suitable clothes; maintain proper positioning when communicating with patients; keep a safe distance; maintain the correct posture; and listen actively. A study by Hill et al showed a 65% reduction in staff injuries, from 2.2 per week to 0.77 per week, during the 1 year intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' satisfaction is a common factor in determining health service center. Many efforts can be done in increasing the quality of health service, from the side of quality improvement of either the staffs or the facility and the environment around the health service, that such good service quality can create healthy and prosperous people (Fraihi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Someone with higher education level can not adjust their expectation with the condition of hospital so that they need higher quality of service to make them feel satisfied. Patients with lower level of education have lower expectation so that they can adjust their expectation in accordance with the condition of hospital as well as accept whatever service given (Fraihi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%